Millennial-Style Nangkring: Millennial Lifestyle Trends, Social Identity, Millennial Characteristics, And Coffee Shop Design - Agustin, Neli; Soleh, Ahmad; Hardinata, Dodi (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The purpose of this study is to understand millennial lifestyle trends, social identity, millennial characteristics, and coffee shop design for millennials, in addition to being a place to gather, do office work, or complete student assignments. Cafes are also often recognized by many people as indicators of social class identity for the younger generation in Bengkulu. This study can also help improve understanding, especially about the phenomenon of human behavior that makes cafes a place to show social class. This study is conducted using phenomenological research and qualitative methodology. The informants are sixty millennials who often spend their free time in high-end cafes, which were the main data sources. Data allocation was spread across six cafes in Bengkulu, which were categorized accordingly. Data collection was carried out through interviews, field observations, and documentation. The analysis stages were carried out. The findings showed that lifestyle trends have a very high level of attraction. In addition, identity and social recognition are very important, because millennials often seek recognition from their friends through hanging out in cafes. Cafes as a second home for millennials who consider cafes to be the most comfortable place to gather and relax, even to do office work to college assignments. an attractive cafe interior design can increase millennial interest in hanging out there. technology and lifestyle of a millennial, seen from how millennials order menus and use technology can reflect their lifestyle. attitude and motivation, millennial attitudes can be seen from the way they interact with cafe staff and enjoy their time there, while their motivation can be influenced by the desire for relaxation and increasing peace of mind and even wanting a high social class from others.